Texas Clipping Effort Doesn’t Leave Placement Tracking to Sheer Luck - Kathleen Phillips (Journal of Applied Communications, 2004)
A goal of Texas A&M University’s Agricultural Communications unit is to regularly place its news in Texas daily papers. By the 1990s, a professional clipping service used for decades had become ineffective. The team noticed that many of the news articles they found in Texas dailies were not received in the monthly clipping service packet. Also, many of the articles received in the packet pertained to items not requested in the keyword list. Handling clips received from the service also was a problem. An in-house clipping service was designed to be a baseline of all agricultural coverage in Texas daily newspapers, including that of the A&M system’s agricultural program. All clips were arranged in an Internet-accessible database from which various statistics could be determined.